PENGARUH MODEL PROBLEM BASED LEARNING DAN KREATIVITAS BELAJAR TERHADAP HASIL BELAJAR PRAKARYA DAN KEWIRAUSAHAAN - Dewintia Rahmi; Khasanah Khasanah (Akademika : Jurnal Teknologi Pendidikan, 2019)
This study aims to examine : 1) differences in result craft and enterpreneurship who learned with Problem Based Learning model that learned with conventional model, 2) the interaction between the use of learning model and students creativity with the results of craft and enterpreuneurship, 3) the differences in learning craft and enterpreuneurship who learned with Problem Based Learning dan conventional learning on student who have high creativity, 4) the differences in learning craft and enterpreuneurship who learned with Problem Based Learning dan conventional learning on student who have low creativity. In this study, there are two independet variables, namely the Problem Based Learning Model and creativity of students, as well as the results of learning craft and enterpreneurship as the dependent variable. This research method using experimental method to desogn factorial 2 x 2 group design that compare two learning model that Problem Based Learning and conventional learning with creativity of students. The sample used was a student of class XI IPA 2 and XI IPA 3 SMAN 8 Bekasi City with of 78 students. Engineering sample are used is random statified.Based on the hypothesis testing results can be summarized as follows : 1) there are differences in learning craft and enterpreunership class in XI SMAN 8 Bekasi City for a given student group Problem Based Learning and conventional learning, 2) there are interaction between learning modeln and students creativity, 3) result craft and enterpreneurship study who have high creativity in the learning process using Problem Based Learning model are higher than using conventional learning model, 4) result craft and enterpreneurship study who have low creativity in the learning process using Problem Based Learning model are lower than using conventional learning model.